Operationalizing the blue economy in the Gulf of Guinea, Africa - Popoola, Olusola Olalekan; Olajuyigbe, Ayo Emmanuel (Frontiers in Political Science, 2023)
The Blue Economy is crucial for sustainable development in Africa. Indeed, essential tools for strategic policy frameworks are being developed for sustainable use and management of ocean resources for improved well-being. The Gulf of Guinea, one of Sub-Saharan Africa's most economically dynamic countries, still needs to overcome challenges such as piracy, security issues, unsustainable anthropogenic activities, and poor institutional frameworks, thus hampering its inability to transition into the Blue Economy. This study assesses the situation of the Blue Economy in the Gulf of Guinea and proposes strategies for its operationalization. A qualitative research approach was used to examine each member state's marine conservation initiatives, regional collaboration, management approaches, and strategic frameworks. Challenges to transitioning into the Blue Economy were identified, leading to the development of a strategic framework for the Gulf of Guinea. The framework aims to deepen gains from traditional-blue-based industries, develop blue-based emerging industries, and foster regional value chains in marine-based products. By harnessing trade investments, improving trade in marine-based products, regional collaboration, and institutionalizing enablers of blue growth, such as marine spatial planning and marine protected areas, the region's marine commons will be conserved, which will enhance the effective operationalization of the Blue Economy in the Gulf of Guinea.